Icariin Alleviates Wear Particle-Induced Periprosthetic Osteolysis via Down-Regulation of the Estrogen Receptor α-mediated NF-κB Signaling Pathway in Macrophages - Guangtao, Fu; Zhenkang, Wen; Zhantao, Deng; Mengyuan, Li; Qingtian, Li; Yuanchen, Ma; Yuanfeng, Chen; Qiujian, Zheng (Frontiers in Pharmacology, 2021)
Periprosthetic osteolysis is one of the major long-term complications following total joint replacement. Its cause is widely accepted to be wear particle-induced activation of inflammatory macrophages. No effective strategy for the prevention and treatment of periprosthetic osteolysis is yet available. Recently, considerable evidence has shown that icariin effectively protects against estrogen deficiency-related bone loss and bone deterioration. However, the molecular mechanism underlying the inhibitory effect of icariin on wear particle-induced periprosthetic osteolysis is not yet clear. In this study, nanoscale CoCrMo wear particles were obtained by high-vacuum three-electrode direct current from the femoral head implant of a patient diagnosed with aseptic loosening. The effects of icariin on wear particle-induced expression of proinflammatory factors, NF-κB signaling modulation, osteolysis, and estrogen receptor α (ERα) activation were evaluated in vitro and in vivo using bone marrow-derived macrophages (BMDMs) and C57/BL6J mice, respectively. A possible link between ERα and the protective effect of icariin was further studied using an ERα antagonist and the ERα-siRNA interference. Chemical composition analysis showed that Cr and Co were the major metallic elements of the nanoscale particles, with a mean size of 150.2±37.4 nm for the CoCrMo particles. Following icariin treatment, significant decreases were observed in CoCrMo wear particle-induced TNF-α and IL-6 mRNA expression in BMDMs, and osteolysis in mice calvaria. Marked decreases in the protein expression level of p-IKKβ, p-p65 and p-IκBα were also observed, together with significant decreases in the nuclear import of P65 and macrophage M1 polarization. RNA sequencing revealed that ERα was closely associated with TNF-α and IL-6 in wear particle-stimulated macrophages. Furthermore, marked increases in phospho-ERα Ser118 and phospho-ERα Ser167 protein expression and the nuclear import of ERα were also found in the icariin group. The protective effects of icariin on CoCrMo particle-induced mouse calvarial osteolysis and on the inflammation response in BMDMs were reversed by ERα antagonist and by ERα-siRNA interference. In conclusion, icariin attenuates wear particle-induced inflammation and osteolysis via down-regulation of the ERα-mediated NF-κB signaling pathway in macrophages. The potential application of icariin as a non-hormonal therapy for wear particle-induced periprosthetic osteolysis is worthy of further investigation.